Investigation on phases transformation and mechanical properties of ductile iron by new heat treatment process / Mohd Faizul Idham Mohd Zulkipli - Mohd Zulkipli, Mohd Faizul Idham (2013)
This study was conducted to investigate quantitatively and qualitatively the matrix compositions and transformations, and to evaluate the correlation between microstructure constituent and material hardness on each sequential stage of new heat treatment process at different temperatures. In addition, the influence of new heat treatment temperature on impact and tensile properties is analyzed. Ductile iron produced by CO2 sand casting method was heat treated by new heat treatment cycle that comprised combination of modified annealing, austenitizing and tempering processes. The new heat treatment process performed was divided into three stages: first stage consists of modified annealing (as-annealed condition); second stage consists of modified annealing and austenitizing processes (as-austenitized condition); and third stage consists of modified annealing, austenitizing and tempering processes (as-tempered condition). A series of microstructure analysis tests, including optical microscopy, X-ray diffractometry, and scanning electron microscopy equipped with energy dispersive X-ray, was applied. Mechanical tests including tensile (ASTM E8M), impact toughness (ASTM-E23-1990) and Vickers hardness test were performed. The results suggest that heat treatment temperature influences the matrix and volume fraction of each phase of ductile iron. Annealing included in new heat treatment process does influence the hardness of ductile iron. Moreover, microstructure constituents have good correlation with mechanical properties. It is proven that, hardness could be estimated using mixture law of hardness for each microstructure constituent. Tensile strength and hardness of ductile iron decrease with decreasing volume fraction of martensite. Increasing ferrite volume fraction results an increasing impact toughness and elongation. The ductile iron treated using this practice is corresponds and equipotential with ADI ‘grade T (ASTM standard A897-90).